Leaf tissue flows and defoliation patterns of Alexandergrass grazed by heifers receiving energy supplement - Paula de Oliveira Severo; Luciana Pötter; Marta Gomes da Rocha; Mateus Negrini; Amanda Carneiro Martini; Vanessa Bayer da Rosa (Acta Scientiarum. Animal Sciences, 2019)
The study was carried out to evaluate defoliation patterns and to quantify leaf tissue flows in Alexandergrass (Urochloa plantaginea (Link.) Hitch) grazed by beef heifers receiving whole rice bran in three levels of supplementation (0, 0.5 and 1 % of body weight). A rotational stocking grazing method and two area replications were utilized. The experimental design was completely randomized following a repeated measure arrangement. The supply of rice bran to heifers grazing Alexandergrass increased the stocking rate by 13%. Regardless of the feeding system, the heifers grazed the expanding leaf blades in the top stratum of the canopy more frequently compared to other types of leaf. Leaf tissue flows, leaf blade intake and grazing intensity have not been changed by supplement fed.